An Assessment of the Literature on Childhood Vaccination from a Behavioural Economics Perspective - Ramzan, Muhammad Javed; Munir, Saqib; Shah, Akram Ali (iRASD Journal of Economics, 2023)
Childhood vaccination is a key public health strategy that safeguards lives and stop the spread of infectious illnesses. Despite the known advantages of vaccination, several nations still have poor immunization rates for children. There has been a rise in focus on concepts of behavioural economics to boost vaccination rates in the recent years. This literature review attempts to provide an overview of the data on behavioural economics interventional ability to boost immunization rates in children. After an extensive examination of electronic databases, we included 44 papers that satisfied the requirements for inclusion in this paper. Various behavioural economics concepts, such as default options, framing and messaging, incentives, and reminder systems, were studied in the study. Overall, the research suggests that raising vaccination rates for children may be accomplished by using behavioural economics concepts. Our review underlines the potential for behavioural economics to raise child immunization rates and provide guidance to academics, politicians, and healthcare professionals on how to create successful immunization programs.